Histological Analysis and Comparison of Endometrial Sampling and Hysterectomy Specimen in Patients with Abnormal Uterine Bleeding - Riaz, Rubina; Sarfraz, Tariq; Riaz, Shahmir; Aneeqa, Saba; Wahid, Yasmin; Afzal, Salma (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency of different causes of Abnormal Uterine Bleeding (AUB) in relation to the age and to determine the degree of concordance in diagnosis on endometrial sampling and hysterectomy specimen with special emphasis on type and FIGO Grade of malignant cases.Study Design: Cross- sectional study.Place and Duration of Study: Histopathology Department, Foundation University Medical College Islamabad Pakistan, from July 2022 to July 2023.Methodology: A total of 321 cases of endometrial sampling were included in the study. Age of the patients along the histological diagnosis was evaluated. Cases that underwent hysterectomy were further compared with the histological outcome.Results: We found that in the premenopausal age group, among 253 cases, chronic endometritis 102(40.3%) was the most common finding followed by endometrial hyperplasia 66(26%) and disordered proliferative endometrium 38(15%). In the post-menopausal age, the incidence of malignancy was quite high (n=39), with endometrioid carcinoma being the most frequent diagnosis 24(61.5%), followed by endometrial hyperplasia. We observed maximum concordance in the histological diagnosis of malignancy between endometrial and subsequent hysterectomy samples. Strong agreement was also detected between endometrioid carcinomas Grade 1(97.4%) and Grade 2(100%).Conclusion: chronic endometritis, endometrial hyperplasia, disordered proliferative endometrium and malignancies are the most common causes of abnormal uterine bleeding. Endometrial sampling emerged as a valuable diagnostic tool, particularly in detecting malignancy.